2008
DOI: 10.1016/j.crci.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Neopeltolide, a new promising antitumoral agent

Abstract: Neopeltolide seems to be a new promising antitumoral agent. The isolation, biological activity, as well as the chemical syntheses of neopeltolide are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…These biological and structural aspects of neopeltolide spurred the interest of synthetic organic chemists. As a consequence, seven total syntheses, including ours, and two formal syntheses have been recorded to date 5–12. In addition, Kozmin and co‐workers have recently reported that synthetic neopeltolide targets cytochrome bc 1 complex and may inhibit mitochondrial Adenosine triphosphate synthesis 8…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…These biological and structural aspects of neopeltolide spurred the interest of synthetic organic chemists. As a consequence, seven total syntheses, including ours, and two formal syntheses have been recorded to date 5–12. In addition, Kozmin and co‐workers have recently reported that synthetic neopeltolide targets cytochrome bc 1 complex and may inhibit mitochondrial Adenosine triphosphate synthesis 8…”
Section: Introductionmentioning
confidence: 86%
“…As a consequence, seven total syntheses, including ours, and two formal syntheses have been recorded to date. [5][6][7][8][9][10][11][12] In addition, Kozmin and co-workers have recently reported that synthetic neopeltolide targets cytochrome bc 1 complex and may inhibit mitochondrial Adenosine triphosphate synthesis. [8] Herein, we describe in detail the total synthesis of the originally proposed (1) and correct (2) structures of neopeltolide by exploiting our newly developed Suzuki-Miyaura coupling/ring-closing metathesis strategy for the synthesis of multi-substituted tetrahydropyrans.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by the efficiency and versatility of the tandem allylic oxidation/oxa‐Michael reaction, we embarked on a stereoselective synthesis of (+)‐neopeltolide macrolactone ( 21 ). The marine macrolide (+)‐neopeltolide ( 19 ) is an extremely potent inhibitor of tumor‐cell proliferation15 and has attracted considerable interest from a number of synthetic research groups 16–18. We envisioned that the embedded 2,6‐ cis ‐4‐hydroxy‐THP could be constructed by using the tandem allylic oxidation/oxa‐Michael reaction as the key bond‐forming step (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…In the past years, neopeltolide has served as an ideal target compound for synthetic chemists to showcase their creativity in how to construct the tetrahydropyran ring in an efficient and stereoselective manner. This review summarizes the total/formal syntheses of neopeltolide, highlighting the synthetic strategies exploited for constructing the tetrahydropyran ring [ 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%